Thoughts on open science, or new trends in publishing the results of pedagogical research - Benedek, András (Central European Journal of Educational Research, 2026)
The radical transformation of education over the past quarter-century, especially accelerated by COVID-19, has raised significant challenges and opportunities for both pedagogical theory and practice. This article examines how the landscape of publishing scientific research—particularly in education—has evolved in response to these changes. Reflecting on more than fifty years in educational research, I explore how digital transformation and Open Science now shape scientific communication and publishing. The introduction reviews the early impulses that shape the theoretical background. It explores new communication forms arising from infocommunication (Katz et al., 2021). Examples show a paradigm shift, demonstrating how scientific communication has adopted online practices. The article highlights conceptual frameworks, spatial and methodological changes in communication, and new ways of sharing research (Nyíri, 2007). It emphasizes the expansion of publication spaces. These changes show that pedagogy researchers must address new issues.